Odontogenic Orofacial Infections. Issue 1 (January 2017) - Bertossi, Dario; Barone, Antonio; Iurlaro, Antonio; Marconcini, Simone; De Santis, Daniele; Finotti, Marco; Procacci, Pasquale
Abstract : Abstract: Acute dental abscess is a frequent and sometimes underestimated disease of the oral cavity. The acute dental abscess usually occurs secondary to caries, trauma, or failed endodontic treatment. After the intact pulp chamber is opened, colonization of the root canals takes place with a variable set of anaerobic bacteria, which colonize the walls of the necrotic root canals forming a specialized mixed anaerobic biofilm. Asymptomatic necrosis is common. However, abscess formation occurs when these bacteria and their toxic products breach into the periapical tissues through the apical foramen and induce acute inflammation and pus formation. The main signs and symptoms of the acute dental abscess (often referred to as a periapical abscess or infection) are pain, swelling, erythema, and suppuration usually localized to the affected tooth, even if the abscess can eventually spread causing a severe odontogenic infection which is characterized by local and systemic involvement culminating in sepsis syndrome. The vast majority of dental abscesses respond to antibiotic treatment, however, in some patients surgical management of the infection may be indicated. In the present work, a retrospective analysis of the patients with dental orofacial infections referred to the Unit of Dentistry and Maxillofacial Surgery of the University of Verona from 1991 to 2011 has been performed.